Treatment and clinical outcomes in anti‐p200 pemphigoid: a systematic review. (9th December 2019) - Laufer Britva, R.; Amber, K.T.; Cohen, A.D.; Kridin, K.
Abstract: Background: Current treatment paradigms in anti‐p200 pemphigoid rely on low levels of evidence, primarily originating from case reports and case series. Objective: To systematically review the utilized treatment modalities for anti‐p200 pemphigoid and to synthesize the available clinical outcomes of treated patients. Methods: We conducted a systematic review of the literature using Ovid‐Medline (1946–2018), Embase (1947–2018) and Web of Science (1900–2018) databases with a broad and inclusive search strategy along with a subsequent search of retrieved articles. All case reports and case series of patients with anti‐p200 pemphigoid were included. Results: Sixty‐eight eligible studies comprising 113 anti‐p200 pemphigoid patients with a mean age of 65.5 years were included in the qualitative synthesis. The clinical outcome of patients following treatment was reported for 91 (80.5%) patients, of whom 83 (91.2%) had achieved complete remission at least once. Complete remission on‐therapy was observed in 51 (56.0%) and complete remission off‐therapy in 12 (13.2%) patients. Thirty‐six (39.6%) patients had experienced at least one flare during the duration of follow‐up. A combination of systemic corticosteroids and adjuvant immunomodulatory agents was the leading therapeutic approach (63.0%) required for disease control. Systemic and topical corticosteroids as monotherapy were sufficient to control the disease in 19.6% and 13.0% of cases, respectively. Dapsone was the most commonly used (41.3%) adjuvant agent. The highest rates of complete remission were achieved in patients managed by systemic corticosteroids as monotherapy (100%) and in those managed by systemic corticosteroids with adjuvant agents (90.7%). Conversely, 45.5% of patients treated only by topical corticosteroids experienced at least one relapse during follow‐up. Conclusion: The vast majority of patients had reached a complete remission during the course of the disease, whereas a considerable proportion of patients experienced at least one relapse. A combination of systemic corticosteroids and adjuvant immunomodulatory agents was the most frequently utilized therapeutic approach.